Analisis Kadar Kalsium (Ca) Pada Lansia Di Panti Perlindungan Dan Rehabilitasi Sosial Lanjut Usia Provinsi Kalimantan Selatan: Analysis of Calsium (Ca) Levels In The Elderly At The “Budi Sejahtera” Social Shalter and Rehabilitation Home For The Elderly in Sout Kalimantan - Amalia, Nurul; Arsyad, Muhammad; Khafifah, Khafifah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
The elderly, or senior citizens, are a group of individuals who have reached old age. People in this age group are usually more susceptible to health problems. Calcium is a nutrient that is essential for the body and is the most abundant mineral found in the body, accounting for approximately 1.5-2% of an adult's body weight or about 1kg. Insufficient or excessive calcium intake can lead to abnormal metabolism. Calcium deficiency can result in osteoporosis and hypocalcemia, while excess calcium can cause hypercalcemia. The purpose of this study is to determine the calcium (Ca) levels in the elderly at the